Functions of truth and justice in the overcoming of grief for forced disappearances’ relatives - Orozco, Rafael Andrés Patiño; Ramos de Farias, Francisco; Chaves, Antonio Marcos (Revista de Psicología Universidad de Antioquia, 2015)